2020
DOI: 10.1111/nyas.14342
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of close faculty−student relationships and mentorship in higher education: findings from the Gallup−Purdue Index

Abstract: College students’ supportive relationships with mentors—professors, advisors, and other caring adults to whom students turn as they develop their interests and career paths—are critical to their development and academic success. The current study sought to explore factors that promote or impede the formation of positive mentor–student relationships during college using a large, nationally representative sample of 5,684 college graduates from the Gallup–Purdue Index. Linear regression models revealed that first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…For example, an institutional natural mentor could advocate for a student who is struggling academically or connect a student with other faculty, helping the student increase their network. However, historically underrepresented college students are less likely to form these institutional mentoring relationships because of systemic barriers in college (Hagler, 2018; Raposa et al, 2020). For example, a national study of middle‐ and high‐school students found that those who had fewer parental resources (e.g., low‐income, lower parental education attainment, parental involvement at school) were less likely to report a school‐based natural mentor compared to those with more parental resources, while controlling for other demographic characteristics, hours worked weekly, and extracurricular activities (Erickson et al, 2009).…”
Section: Historically Underrepresented College Studentsmentioning
confidence: 99%
“…For example, an institutional natural mentor could advocate for a student who is struggling academically or connect a student with other faculty, helping the student increase their network. However, historically underrepresented college students are less likely to form these institutional mentoring relationships because of systemic barriers in college (Hagler, 2018; Raposa et al, 2020). For example, a national study of middle‐ and high‐school students found that those who had fewer parental resources (e.g., low‐income, lower parental education attainment, parental involvement at school) were less likely to report a school‐based natural mentor compared to those with more parental resources, while controlling for other demographic characteristics, hours worked weekly, and extracurricular activities (Erickson et al, 2009).…”
Section: Historically Underrepresented College Studentsmentioning
confidence: 99%
“…Often provided at an institutional level (Raposa et al, 2021) or through established formal or informal (Hernandez et al, 2017;Law et al, 2020), mentorship is valuable to student success. Law et al's (2020) review breaks down the various mentorship approaches, including psychosocial, formal, and theoretical.…”
Section: Mentorship As a Means Of Student Developmentmentioning
confidence: 99%
“…The same mentoring program can achieve markedly different outcomes depending on the age and cultural and demographic background of the participants. 11,61 We know, for example, that mentees' decisions to study a STEM field were more strongly influenced by mentoring experiences when they were not the children of parents working in a STEM field. 62 The areas and domains in which programs are situated also vary considerably and influence how effective chosen approaches to mentoring will turn out to be.…”
Section: Key Issue 3: Consideration Of Idiographic Program Characterimentioning
confidence: 99%
“…Idiographic aspects include, for example, the target groups, the mentors and mentees who are participating in a given program, and the context in which a given program is being implemented. The same mentoring program can achieve markedly different outcomes depending on the age and cultural and demographic background of the participants 11,61 . We know, for example, that mentees’ decisions to study a STEM field were more strongly influenced by mentoring experiences when they were not the children of parents working in a STEM field 62…”
Section: Seven Key Issues In Professionalizing Mentoring Practicesmentioning
confidence: 99%